NERDS : National Espionage, Rescue, and Defense Society - Buckley, Michael 1969-; Beavers, Ethen (New York : Amulet Books, 2009)
While running a spy network from their elementary school, five unpopular misfits combine their enhanced abilities and use cutting-edge gadgetry to fight evil around the world.
Accelerated Reader AR